Study on system upgrading for Supervisory Control and Data Acquisition (SCADA) at Rasa Water Treatment Plant (RWTP) / Suhaila Musa - Musa, Suhaila (2009)
The implementation of new version monitoring and control system in water treatment plant can increase the quality of supervision, production and monitor quality of water accurately without involve a large number of man power. This study is based on solving the real industrial problem by studying the effect of new Supervisory Control and Data Acquisition (SCADA) system implementation on Rasa Water Treatment Plant (RWTP) for increased production clear water with minimum man power, high accuracy and efficiency. The objectives are to study, evaluates and propose the new suitable of SCADA system for implementation in RWTP. The result is based on analysis of existing RWTP data using the existing SCADA system and expected result based on latest version of SCADA system implementation proposed on RWTP. The efficiency and potential of new proposed SCADA system has been compared and analyze based expected production projection and financial projection. Preventive maintenance has been highlighted in future recommendation as a precaution to maintain and optimize the new version of SCADA system for increase the RWTP production and optimize the financial projection.